Palaeoecology of well-preserved coral communities in a siliciclastic environment from the Late Pleistocene (MIS 7), Kish Island, Persian Gulf (Iran): The development of low-relief reef frameworks (biostromes) in increasingly restricted environments - Mossadegh, Z.; Parker, J.; Gischler, E.; Oschmann, W.; Blakeway, David; Eisenhauer, A. (Springer, 2013)
Major changes in community structure and depositional relief of high-latitude coral communities in the southern Persian Gulf between marine isotope stage (MIS) 7 and the present day suggest that the area has become increasingly restricted. Corals and bivalves from outcrops on Kish Island, Iran, were identified in order to interpret the Late Pleistocene palaeoenvironmental setting. U/Th disequilibrium dating was used to constrain the ages of the stratigraphic units. During MIS 7, two coral-bearing sequences were deposited on what is now Kish Island. The lower sequence is dated as MIS 7. 5 and changes laterally from an assemblage dominated by Cyphastrea sp. and Platygyra daedalea in the west to one characterized by branching Montipora in the east. By contrast, the upper sequence, dated as MIS 7. 1, transitions from an assemblage dominated by platy Montipora in the west to a diverse assemblage of Platygyra and other faviids in the east. The assemblages of both sequences are within a marl matrix and bounded by thin lithified mollusc-rich layers. Corals and bivalves indicate that the sequences were deposited on gentle slopes in sheltered environments less than 20 m deep. The MIS 7 deposits may be classified as coral carpets or biostromes that developed a low-relief framework. During MIS 5, coral communities were no longer framework building and are now limited to an Acropora-rich layer of coral rubble that covers large parts of the island, and two small incipient reefs with sparse faviids. Similarities between the MIS 5 and modern nearshore coral communities suggest that the environmental conditions during MIS 5 were comparable to those of today. The late Pleistocene coral carpets and non-framework coral communities of the southern Persian Gulf may serve as models for coral biostromes in the fossil record, which formed under restricted environmental conditions such as elevated terrigenous input, high turbidity, and strong seasonal changes in temperature and/or salinity.